2022
DOI: 10.1051/0004-6361/202142846
|View full text |Cite
|
Sign up to set email alerts
|

Updated Gaia-2MASS 3D maps of Galactic interstellar dust

Abstract: Aims. Three-dimensional (3D) maps of Galactic interstellar dust are a tool for a wide range of uses. We aim to construct 3D maps of dust extinction in the Local Arm and surrounding regions. Methods. To do this, Gaia EDR3 photometric data were combined with 2MASS measurements to derive extinction towards stars with accurate photometry and relative uncertainties on EDR3 parallaxes of less than 20%. We applied our hierarchical inversion algorithm adapted to inhomogeneous spatial distributions of target stars to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 25 publications
2
78
1
Order By: Relevance
“…In the vicinity of the Sun, many of the major star-forming regions are associated with long, filamentary, molecular-cloud structures (e.g., Jackson et al 2010;Goodman et al 2014;Zucker et al 2015;Green et al 2019;Lallement et al 2019Lallement et al , 2022Alves et al 2020;Zucker et al 2020). One of these filaments is a kiloparsec-long collection of molecular clouds and star-forming regions, traditionally considered to be part of the Milky Way's Sagittarius Arm, but shown by Gaia to form a discrete substructure with a high-pitch angle relative to the arm (Kuhn et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…In the vicinity of the Sun, many of the major star-forming regions are associated with long, filamentary, molecular-cloud structures (e.g., Jackson et al 2010;Goodman et al 2014;Zucker et al 2015;Green et al 2019;Lallement et al 2019Lallement et al , 2022Alves et al 2020;Zucker et al 2020). One of these filaments is a kiloparsec-long collection of molecular clouds and star-forming regions, traditionally considered to be part of the Milky Way's Sagittarius Arm, but shown by Gaia to form a discrete substructure with a high-pitch angle relative to the arm (Kuhn et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Such structures have been investigated in OB stars (Pantaleoni González et al 2021) and signatures of varying oscillation amplitudes across stars of different ages (5-100 Myr) are present across the disk (Thulasidharan et al 2022). Global corrugations in the dust map of Lallement et al (2022) have also been found, including regions along the Orion arm in the second quadrant and in the Sagittarius-Carina arm in the first and fourth quadrants.…”
Section: Discussionmentioning
confidence: 99%
“…The precise astrometry measured for over one billion stars by the ESA Gaia mission (Gaia Collaboration 2021) has transformed our understanding of the Milky Way's structure and the ability to measure the distances and reddening for millions of stars near the Sun accurately has unveiled the local interstellar medium (ISM) in three dimensions (Green et al 2019;Lallement et al 2019Lallement et al , 2022Chen et al 2019;Rezaei et al 2020;Leike et al 2020). Recently, Alves et al (2020) discovered a ∼3 kpc long, narrow (aspect ratio of 1:20), and undulating gas structure they named the Radcliffe wave, connecting many nearby star-forming complexes (CMa, MonR2, Orion, Taurus, Perseus, Cepheus, North America nebula, and Cygnus) into a quasi-linear feature on the XY plane of the Galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Gaia data on stellar distances in particular (e.g., Gaia Collaboration 2016; Gaia Collaboration 2021; Bailer-Jones et al 2021) have allowed for the precise localization in 3D space of pelgrims@physics.uoc.gr more than one billion of stars in our Galaxy through the accurate determination of stellar parallaxes. Coupling measurements of stellar parallaxes to reddening, Bayesian inversion methods have already been successful in reconstructing 3D maps of the dust density distribution (e.g., Green et al 2019;Lallement et al 2019;Leike & Enßlin 2019;Leike et al 2020), leading to stunning 3D images mapping the dust content of the ISM, in the Solar neighbourhood from within the first tens of parsec and up to much larger distances within the Galactic disk, already covering a substantial fraction of the Galaxy (6000 × 6000 × 800 pc 3 for Lallement et al 2019Lallement et al , 2022. Such 3D mappings of the ISM content are of great interest for several areas in Astrophysics.…”
Section: Introductionmentioning
confidence: 99%
“…They shed new light on the dynamics shaping the Galaxy, breaking degeneracies caused by 2D mapping on the 3D shapes of Article number, page 1 of 28 ISM clouds and cloud complexes, their formation mechanisms, and their history (e.g., Ivanova et al 2021;Bialy et al 2021;Rezaei Kh. & Kainulainen 2022;Zucker et al 2022;Lallement et al 2022;Konstantinou et al 2022). Ultimately, 3D images of the dust content of the Galaxy could also help in the characterization of Galactic foregrounds for observational cosmology and extragalactic astrophysics (e.g., Martínez-Solaeche et al 2018).…”
Section: Introductionmentioning
confidence: 99%